THE PURCHASE DECISION OF SAMSUNG BY GENERATION Z IN LAWEYAN DISTRICT VIEWED FROM LIFESTYLE, BRAND IMAGE AND BRAND AWARENESS - Yola Rizky Ning Tyas; Bambang Mursito; Fithri Setya Marwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Among the many Samsung enthusiasts, one of them is Generation Z who was born in 1995-2010, now it is one of the generations that are constantly required to keep abreast of endless technological developments. Laweyan District as one of the areas in Surakarta City has many educational institutions and business units with a large number of generation Z, both natives and immigrants from outside the city of Laweyan District with different consumptive behavior in choosing smartphone. This study aimed to ascertain the impact of lifestyle, brand image, and brand awareness on purchase decision. This research is quantitative descriptive with 100 respondents taken using purposive sampling technique. Data analysis techniques include the classic assumption test, f test, multiple linear regression, t test, and coefficient of determination. The results of this research indicate that lifestyle, brand image and brand awareness have a positive and significant effect on Samsung purchase decisions by Generation Z in Laweyan District. Keywords: Lifestyle, Brand Image, Brand Awareness, Purchaseh Decisions, Generation Z